Perception Assessment of Guidance and Counseling Services among Educational Stakeholders in Selected Secondary Schools in Oyo State, Nigeria - Muraina Kamilu Olanrewaju; Yusuf Suleiman (Universitas Mathla'ul Anwar Banten, 2019)
Guidance and Counseling is a service that all human beings need at one point of their life. There is no human being that has never got a problem at one point or another. This study focused on the assessment of perception of guidance and Counseling services among educational stakeholders in selected secondary schools in Oyo State, Nigeria. Descriptive research design of ex-post-facto type was used in the study. Simple and purposive sampling techniques were used in sampling 300 participants from 10 local government areas (50 schools) in Oyo state. The respondents were measured with validated scale of 0.91 reliability coefficient and the data obtained was analyzed using simple percentage statistical analysis. Three (3) research questions were raised and answered. The results showed that school administrators, teacher and parents (educational stakeholders) had negative perception of guidance and Counseling services. In view of these findings, the study recommended that educational stakeholders need guidance in order to understand and appreciate guidance and Counseling services and that parents should be made to realize that the times are fast changing and that they have to gradually change from the old ways so as to change positively to guidance and Counseling services.